ROLE OF DIACERIN IN DIFFERENT GRADES OF OSTEOARTHRITIS - NASEER , MK; FAISAL , S; BUTT , AB; AHMAD , B; RAO , MA; ASIF , S; ALI , A; AKRAM , S; ARSHAD , A (Biological and Clinical Sciences Research Journal, 2023)
Osteoarthritis (OA) is a joint disease that causes pain and degeneration in the affected area. There are no standard guidelines for agents that can slow down or modify the disease’s progress. Diacerin is one such agent used to improve symptoms of OA. The objective was to analyze its efficacy in different grades of OA. A quasi-experimental study was conducted at Ghurki Trust Teaching Hospital in Lahore over six months from Jan 2023 to July 2023. After obtaining informed consent and meeting inclusion and exclusion criteria, we included 78 patients with grade II and III OA (39 each). All patients were given Diacerin (100mg twice daily). The baseline Western Ontario and McMaster Universities Arthritis Index (WOMAC) and pain on the Visual Analogue Scale (VAS) were used to measure the treatment’s efficacy in improving symptoms after six months. The data was analyzed using SPSS 23.0. The mean age of the participants was 53.98+6.17 years. The mean WOMAC score was 49.62+7.81 before treatment, which decreased significantly to 38.34+8.79 after six months of treatment (p-value <0.05). The mean VAS score before and after treatment was 7.41+0.98 and 4.82+1.07, respectively. These findings suggest that Diacerein significantly reduces pain and improves functional ability in patients with OA of the knee joint. This treatment was safe and well-tolerated. Its use is recommended in early grades of OA.